2018
DOI: 10.1262/jrd.2018-024
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte-specific gene <i>Oog1</i> suppresses the expression of spermatogenesis-specific genes in oocytes

Abstract: Oog1, an oocyte-specific gene that encodes a protein of 425 amino acids, is present in five copies on mouse chromosomes 4 and 12. In mouse oocytes, Oog1 mRNA expression begins at embryonic day 15.5 and almost disappears by the late two-cell stage. Meanwhile, OOG1 protein is detectable in oocytes in ovarian cysts and disappears by the four-cell stage; the protein is transported to the nucleus in late one-cell to early two-cell stage embryos. In this study, we examined the role of Oog1 during oogenesis in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…TEKT2 belongs to Tektin family, which is important in cytoskeleton formation [ 12 ]. Several studies have reported its role in spermatogenesis [ 13 , 14 ]. However, its role in cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TEKT2 belongs to Tektin family, which is important in cytoskeleton formation [ 12 ]. Several studies have reported its role in spermatogenesis [ 13 , 14 ]. However, its role in cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout and transgenic mice are frequently employed to analyze the function of maternal factors [ 8 , 9 , 10 , 11 ]. However, these genetically modified techniques can be time-consuming and require the management of large numbers of animals.…”
mentioning
confidence: 99%
“…A few maternal-specific genes have been identified and shown to significantly impact early embryonic development. For example, in mouse embryogenesis, maternal-specific factors Zar1 7 and Npm2 8 play roles in the 1-2 cell embryo, and Mater 9 , Zfp36l2 10 , and Oog1 11 function in the 2-4 cell embryo, as well as Stella, which is involved in the morula development 12 . Several functional maternal-specific factors have been reported in zebrafish embryogenesis, including Foxr1 13 , Kpna7 14 , Slbp2 15 , Fue 16 , Plk1 17 , and Fhdc3 14 .…”
Section: Introductionmentioning
confidence: 99%